Tropical agroecosystem functions in a changing environment - Holle, MJM (2022)
In many tropical regions, forests have been extensively converted to various land uses, notably through the expansion of agriculture. Both biodiversity and associated ecosystem functions and services have been eroded in these human-modified tropical landscapes. My research investigates the effects of land-use change on invertebrate communities and ecosystem functioning from both fundamental and applied ecological perspectives, as well as the risks posed by global environmental change, mainly agriculture and climate change in tropical ecosystems. I focus on a human-modified tropical forest landscape associated with Panua Nature Reserve in Sulawesi, Indonesia. Despite its protected status, Panua Nature Reserve has seen extensive human disturbance, resulting in a mixture of forest, shrubland, and maize fields within the reserve. My study area is a tropical landscape shaped by small-scale farming. Small-holder farmers constitute the majority of tropical farmers and are severely marginalised.